Desempenho de movimentos cíclicos e discretos realizados em tarefa de fitts simulada em computador - Balio, Tiago Cesar; Dascal, Juliana Bayeux; Marques, Inara; Rodrigues, Sergio Tosi [UNESP]; Okazaki, Victor Hugo Alves (My University, 2013)
This study compared the performance of cyclical and discrete movements in Fitts’ task simulated by a computer. Twenty male adults, between 25 and 30 years old, participated as volunteers in the study. The software Discrete Aiming Task (v.2.0) simulated the Fitts’ task, in the discrete and cyclical conditions, and provided the movement time (TM). It was manipulated 4 target widths and 3 distances between the targets to provide index of difficulties (ID) from 1 to 6 bits. The ANOVA TWO WAY, 3 (Conditions) x 6 (ID), with repeated measures in the last factor, compared the TM in the different conditions. Regression analysis verified the relationship between TM x ID. There were no significant differences between the conditions; the virtual environment and the mouse were used to explain such results. All movement conditions showed a straight relationship between TM x ID with R²>0.990. Therefore, Fitts’ law showed to be consistent, independently of the movement strategy performed.
Performance of cyclical and discrete movements executed in Fitts’ task simulated by computer
Keywords: Cyclical movement; Discrete movement; Fitts` law; Motor control; Speed-accuracy tradeoff